Pendampingan Pembuatan Nomor Induk Berusaha (NIB) di Kecamatan Sukoharjo Kabupaten Sleman - Hasanah, Hani Nur; As'ari, Hasim (Universitas Pahlawan Tuanku Tambusai, 2026)
Business legality is an important component in strengthening the sustainability of Micro, Small, and Medium Enterprises (MSMEs). One essential form of legality that every business actor must have is the Business Identification Number (NIB), issued through the Online Single Submission Risk-Based Approach (OSS-RBA) system. The NIB functions as a legal identity and a basis for obtaining government facilities and protection. This community service activity was carried out in Sukoharjo District, Sleman Regency, involving two local business partners, Storytime and Warmindo Kang Ali. The aim was to provide counseling and technical assistance on the NIB registration process so that business actors can independently manage their legality. The methods included observation, interviews, and direct guidance. The results showed an increase in understanding and skills in managing business legality, as well as higher legal awareness and independence in supporting a competitive and sustainable business ecosystem.